Subnational Competitiveness and National Performance: Analysis and Simulation for Indonesia - Tan, Khee Giap; Amri, Mulya (Pontificia Universidad Católica del Perú. CENTRUM, 2013)
The stable growth of Indonesia’s economy over the past eight years has provided momentum for investment in the country. One of the approaches taken by the central government is to allow healthy competition between its provinces. The Asia Competitiveness Institute (ACI) responds positively to that policy by ranking the competitiveness of Indonesia’s 33 provinces and providing simulation studies on how to improve each province’s competitiveness. ACI takes a comprehensive approach to the notion of provincial competitiveness, dissecting it from four major environments: macroeconomics, microeconomics, governance, and quality of life. Drawing on 91 indicators from formal sources as well as ACI’s own surveys and interviews, the study aggregates the indicators into 12 sub-environments, reaggregates them into four environments, and finally reaggregates them again into an overall competitiveness index. The conclusion highlights the high level of competitiveness in provinces where the country’s major urban regions are situated, as well as those closest to Singapore as the regional trading hub. Provinces endowed with natural resources also have the opportunity to be competitive, but not if they are wanting in aspects such as governance and quality of life. The study’s findings invite further research on more specific topics such as labor market flexibility and regional cooperation.
Keywords: Indonesian provinces; Competitiveness ranking; Simulation studies; Subnational competitiveness; https://purl.org/pe-repo/ocde/ford#5.02.04